Effects of a multidisciplinary quality of life intervention on sleep quality in patients with advanced cancer receiving radiation therapy. Issue 3 (June 2020) - Gentry, Melanie T.; Atherton, Pamela J.; Lapid, Maria; Rosen, Preetha Sharone; Kung, Simon; Richardson, Jarrett; Niazi, Shehzad K.; Bobo, William V.; Clark, Matthew M.; Rummans, Teresa A.
Abstract: Objectives: Sleep disturbances are prevalent in cancer patients, especially those with advanced disease. There are few published intervention studies that address sleep issues in advanced cancer patients during the course of treatment. This study assesses the impact of a multidisciplinary quality of life (QOL) intervention on subjective sleep difficulties in patients with advanced cancer. Method: This randomized trial investigated the comparative effects of a multidisciplinary QOL intervention ( n = 54) vs. standard care ( n = 63) on sleep quality in patients with advanced cancer receiving radiation therapy as a secondary endpoint. The intervention group attended six intervention sessions, while the standard care group received informational material only. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS), administered at baseline and weeks 4 (post-intervention), 27, and 52. Results: The intervention group had a statistically significant improvement in the PSQI total score and two components of sleep quality and daytime dysfunction than the control group at week 4. At week 27, although both groups showed improvements in sleep measures from baseline, there were no statistically significant differences between groups in any of the PSQI total and component scores, or ESS. At week 52, the intervention group used less sleep medication than control patients compared to baseline ( p = 0.04) and had a lower ESS score (7.6 vs. 9.3, p = 0.03). Significance of results: A multidisciplinary intervention to improve QOL can also improve sleep quality of advanced cancer patients undergoing radiation therapy. Those patients who completed the intervention also reported the use of less sleep medication.